PENGGUNAAN PLATFROM YOUTUBE UNTUK PENGEMBANGAN BERPUISI PADA SISWA KELAS VI SDN RAGAS - Desti Endrawati Subroto; Teddy Hidayatullah; Nuraliyah Nuraliyah (Jurnal Ilmiah Pendidikan dan Keislaman, 2026)
This research is motivated by the low interest and poetry skills among sixth-grade students at SDN Ragas 3, caused by a tendency to prioritize gaming and random video consumption on mobile devices over educational use. This study aims to familiarize students with YouTube as an audiovisual learning platform to develop their skills, specifically in poetry. The research method employed was Classroom Action Research (CAR), conducted over two cycles. Research instruments included observation sheets, performance tests, and documentation. The results indicated a significant improvement in students' poetry skills, with the class average score increasing from 65 in the pre-cycle stage to 85 at the end of Cycle II. Furthermore, this method proved effective in enhancing poetry skills as it allowed students to observe practical examples and encouraged them to perform. In conclusion, the use of the YouTube platform is effective in developing the poetry skills of sixth-grade students at SDN Ragas 3, while providing an interactive learning medium that is relevant to digital technology advancements